Valuation Response to New Information: A Test of Resource Mobility and Market Structure - Lustgarten, Steven H.; Thomadakis, Stavros B. (Journal of Political Economy, 1980)
This article hypothesizes that resources employed in concentrated industries are more specialized and durable and therefore less mobile than resources employed in atomistic industries. The hypothesis is tested by estimating the relationship between changes in the market value of a firm's securities and changes in its earnings levels and comparing this relation under different market structures. The response of market values to earnings changes is found to be greater for concentrated industries than for atomistic industries. This difference is interpreted as evidence that abnormal earnings persist longer in concentrated industries because of the lower degree of resource mobility.